Learning in the context of work in a digital age : the use of digital media in informal and formal learning contexts - Ang , Sin Sing [Verfasser]; Orozco, Mariana [Verfasser]; Gijbels, David [Verfasser]; Van den Bossche, Piet [Verfasser] (My University, 2018)
"Technology, and more specifically digital media, has opened up seemingly infinite possibilities for learning to take place beyond the classroom and for crossing from informal to formal learning. The goal of this study is to understand how adult 'learners at work' use digital media in formal and informal learning contexts. A total of 44 adults enrolled in various executive programmes participated in a survey research. Results suggest that, among various activities responding to pedagogical categories, those activities learners engage the most in are 'referential individual', 'constructive collaborative' and 'reflective collaborative'. Learners engage more frequently in activities belonging to wider pedagogical categories when they are part of work-related contexts (predominantly informal) than it is the case in more formal contexts. Using digital media, a continuum of learning contexts could be encouraged through 'referential', 'constructive' and 'reflective' activities, be it on a progressive basis from individual to collaborative." (Author's Abstract ; BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; L 4.2.3 Internetbasiertes Lernen / E-Learning; Informelles Lernen; Lebenslanges Lernen; Digitale Medien; E-Learning; Lernen am Arbeitsplatz; Erwachsenenbildung; Mediennutzung